ATTENTION AND COGNITIVE FUNCTIONING IN ADULTS WITH DOWN SYNDROME: A COMPARISON WITH TYPICALLY DEVELOPING ADULTS - Physio, Dimple Choudhry; E, Ekta; M, Malika; Mohammad, Zafar (MNJ (Malang Neurology Journal), 2026)
Background: Down syndrome (DS) is the most common chromosomal disorder associated with intellectual disability, characterized by distinctive neurocognitive profiles and an increased risk of early-onset dementia. While much research has focused on children and adolescents with DS, fewer studies have systematically examined the attention span and cognitive function of adults with DS compared to typically developing adults of the same age. Understanding these differences is crucial for designing appropriate interventions, educational programs, and long-term care strategies. Objective: The objective of this study is to examine the differences in attention span and cognitive function between adults with Down syndrome and healthy individuals. This study aims to identify the underlying neurological, genetic, and physiological factors contributing to these differences. Methods: A total of 25 adults with Down syndrome, aged 18 to 25 years, were recruited from SIRTAR School in Rohtak District, Haryana. Cognitive function was assessed using the Cognitive Scale for Down Syndrome, while attention span was measured using the Stroop Color and Word Test. Results: Statistical analysis of data was performed using SPSS software version 21.0. Continuous variables were presented as mean ± SD. independent t-test were used for between group analysis. For all statistical tests, a p-value of ≤0.05 was taken as a significant difference. Analysis revealed statistically significant group differences across all cognitive domains. Adults with DS scored significantly lower than controls on CS-DS subscales: EFD (p = 0.00), LD (p = 0.00), MD (p = 0.00), and CS-DS total (p = 0.00). Stroop test findings further demonstrated marked deficits in attention span, with significant differences in correct responses (p = 0.00), incorrect responses (p = 0.00), no responses (p = 0.00), congruent response time (p = 0.00), and incongruent response time (p = 0.00) between the DS and control groups. Conclusion: Adults with Down syndrome exhibit differences in attention span and cognitive function compared to healthy individuals due to genetic, neurological, and physiological factors. Structural and functional variations in the brain.